2021
DOI: 10.3390/s21237977
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of CO, NO2, and O3 Using Airify: A Low-Cost Sensor Cluster for Air Quality Monitoring

Abstract: During the last decade, extensive research has been carried out on the subject of low-cost sensor platforms for air quality monitoring. A key aspect when deploying such systems is the quality of the measured data. Calibration is especially important to improve the data quality of low-cost air monitoring devices. The measured data quality must comply with regulations issued by national or international authorities in order to be used for regulatory purposes. This work discusses the challenges and methods suitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Interestingly, the KNN method presents results close to the best despite its simplicity, although with a higher standard deviation, which can represent unwanted performance variability with small perturbation to the training and test data. These results are in line with other results reported in the literature relating appealing results of ensemble methods in calibrating air quality sensors [ 32 , 33 , 34 , 36 , 37 ], confirming the nonlinear behavior of these devices.…”
Section: Results and Discussionsupporting
confidence: 92%
“…Interestingly, the KNN method presents results close to the best despite its simplicity, although with a higher standard deviation, which can represent unwanted performance variability with small perturbation to the training and test data. These results are in line with other results reported in the literature relating appealing results of ensemble methods in calibrating air quality sensors [ 32 , 33 , 34 , 36 , 37 ], confirming the nonlinear behavior of these devices.…”
Section: Results and Discussionsupporting
confidence: 92%
“…An artificial neural network was used to calculate this calibration function. Neural networks are a fundamental tool in the field of low-cost-sensor calibration [ 25 , 26 , 27 , 28 ]. In a previous work [ 29 ], we tested this type of algorithm against other common techniques and concluded that neural networks performed the best.…”
Section: Methodsmentioning
confidence: 99%
“…80-1542) with the main diffraction peaks at 31.17 • , 36.72 • , 44.66 • , 59.15 • and 65.00 • corresponding to (220), (311), (400), ( 511) and (440) planes, respectively [25,26]. The lattice parameters of the Co 3 O 4 nanoparticles were a = b = c = 0.81099 nm, while the cell volume was 0.53339 nm 3 . Regarding Scherrer's formula applied in the main peak (311), the crystallite size of the Co 3 O 4 nanoparticle was found to be 43.7 nm.…”
Section: Structural and Morphological Properties Of Powder And Sensin...mentioning
confidence: 99%
“…Previously, only bulky industrial grade gas sensors could be found on the market, however, nowadays, advances in gas sensing technology and materials have sparked the creation of low-cost, low-power, small form factor sensors. Use cases include systems applied in smart cities for the purpose of gas pollution monitoring for health reasons, or in factories for gas-leak detection for safety reasons [3].…”
Section: Introductionmentioning
confidence: 99%